Association mapping of lignin response to Verticillium wilt through an eight-way MAGIC population in Upland cotton - Xiao-min TIAN; Peng HAN; Jing WANG; Pan-xia SHAO; Qiu-shuang AN; Nurimanguli AINI; Qing-yong YANG; Chun-yuan YOU; Hai-rong LIN; Long-fu ZHU; Zhen-yuan PAN; Xin-hui NIE (Journal of Integrative Agriculture)
Lignin metabolism plays a pivotal role in plant defense against pathogens and is always positively correlated as a response to pathogen infection. Thus, understanding resistance genes against plant pathogens depends on a genetic analysis of the lignin response. This study used eight Upland cotton lines to construct a multi-parent advanced generation intercross (MAGIC) population (n=280), which exhibited peculiar characteristics from the convergence of various alleles coding for advantageous traits. In order to measure the lignin response to Verticillium wilt (LRVW), the artificial disease nursery (ADN) and rotation nursery (RN) were prepared for MAGIC population planting in four environments. The stem lignin contents were collected, and the LRVW was measured with the lignin value of ADN/RN in each environment, which showed significant variations. We employed 9 323 high-quality single-nucleotide polymorphism (SNP) markers obtained from the Cotton-SNP63K array for genotyping the MAGIC population. The SNPs were distributed through the whole genome with 4.78 SNP/Mb density, ranging from 1.14 (ChrA06) to 10.08 (ChrD08). In addition, a genome-wide association study was performed using a Mixed Linear Model (MLM) for LRVW. Three stable quantitative trait loci (QTLs), qLRVW-A04, qLRVW-A10, and qLRVW-D05, were identified in more than two environments. Two key candidate genes, Ghi_D05G01046 and Ghi_D05G01221, were selected within the QTLs through the combination of variations in the coding sequence, induced expression patterns, and function annotations. Both genes presented nonsynonymous mutations in coding regions and were strongly induced by Verticillium dahliae. Ghi_D05G01046 encodes a leucine-rich extensin (LRx) protein involved in Arabidopsis cell wall biosynthesis and organization. Ghi_D05G01221 encodes a transcriptional co-repressor novel interactor of novel interactor of jasmonic acid ZIM-domain (JAZ–NINJA), which functions in the jasmonic acid (JA) signaling pathway. In summary, the study creates valuable genetic resources for breeding and QTL mapping and opens up a new perspective to uncover the genetic basis of VW resistance in Upland cotton.